Tratamiento de los activos fijos tangibles y su efecto en la situación financiera de la empresa agroindustrial Cartavio S.A.A - Avila Arteaga, Walter Eyner (2017)
The research problem is referred to as the treatment of tangible fixed assets affect the Financial Situation of the Agroindustrial Enterprise Cartavio SAA, The objective that guided the investigation was the determination of the degree of incidence that the Tangible Assets have in the Financial Situation of a company Agroindustrial. The present research has as a study population the Agroindustrial Company Cartavio S.A.A having as tangible fixed assets. The method used was the Inductive-Deductive. The techniques used were interviews, surveys and documentary analysis; For which data collection instruments such as the interview guide, survey questionnaire, economic and financial information of the company were used. Among the main results it is observed that Tangible Fixed Assets increase from one period to another, this is due to the great importance they have within the company, the most outstanding assets and where the main source of investment is generally represented are the Machinery And Equipment, Land, Vehicles and Buildings and other Constructions, all these have a great variation, these assets except the land are depreciated with the Straight Line Method because it is their continuous production. Finally, it is concluded that the degree of incidence of Tangible Fixed Assets in the Financial Position is very relevant since it represents the largest source of investment made by the company, on the other hand it is concluded that its accounting treatment is related to technical information framed in the Accounting Plan and new procedures were proposed in order to have better control and provide real and reliable data.